Managing Communication Anxiety among Foreign Language Learners in Conversation Classes (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The study delves into speaking anxiety among English as a Foreign Language (EFL) students, exploring the hurdles faced in their speaking abilities. With a focus on the factors influencing speaking performance, the research investigates the impact of anxiety on effective communication in English language classes. Conducted at the Department of English for Girls, University of Kufa, the investigation aims to identify speaking AnxietyAnxiety as a pivotal determinant shaping learners' attitudes in English language classes. Employing a descriptive qualitative methodology, the research administered a closed-ended questionnaire in paper format to students. The questionnaire, designed to elicit responses through predefined options where participants indicated their choices by ticking designated columns, examined various aspects influencing speaking performance and evaluated the effectiveness of strategies in enhancing English proficiency among EFL students. The findings reveal the presence of anxiety factors within the classroom environment, stemming from reasons such as students' lack of confidence, fear of verbal errors, and reluctance to communicate proficiently in English.Moreover, the study highlights EFL learners' communication challenges in English language classes. Moreover, the present study explored the construct of speaking-in-class AnxietyAnxiety of KUFA EFL undergraduate students. It aimed to identify speaking anxiety as an essential factor in learners' attitudes towards English. It also tried more specifically to find out the situations that provoked fear.